Effect of Organic Content in River Sediment on the Number and Size of Corbicula Fluminea - Bibi Zafirah Zaki, Nur Afiqah Zulkiffilee, Zulhazman Hamzah, Aweng A/L Eh Rak (International Journal of Advanced Science and Technology, 2020)
Corbicula fluminea is popularly known as “Etak” in the Kelantanese dialect or known as Asian clams. These species can be found living in the sandy bottom of main rivers in Malaysia. C. fluminea is a very popular food because local people eaten C. fluminea as snack. The river where the etak is located, usually receives nutrients that are carried along with the runoff and these nutrients are considered pollutants to the river water. However, nutrient is also a source of food in the sediment for aquatic life especially C. fluminea. Plus, the size and also number of C. fluminea present was believed to be influenced by organic content in sediment. Hence, the objective of this study is to determine and correlate the concentration of organic matter with the number and size of C. fluminea at one river in Kelantan. The C. fluminea samples were collected from two points at Lubuk Lepah River, Kelantan which is six composites sampling of sediment and six sampling of C. fluminea. Thus, the organic matter in sediment was carried out by using Loss on Ignition (LOI) analysis. The results showed that, the size and number of “etak” does not correlate with the percentage of organic matter but the results show that “etak” can survive and growth with organic contents as low as 0.12%. These findings can be used as a basis for the Authority to breed and cultivate “etak” to meet the needs of sellers and consumers in Kelantan. In the meantime, it can increase the income of the C. fluminea seller or vendor.Keywords: Corbicula fluminea, river sediment, organic matter, number, size.